Evaluation of tuberose (Polianthes tuberosa L.) genotypes under coastal ecosystem of Tamil Nadu - C T Sathappan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2018)
Genetic variability existing among genotypes is the prime and basic factor for the improvement of any character in a successful breeding programme of tuberose (Polianthes tuberosa L.). Though the attempts made so far to exploit the available variability have culminated in the release of a few improved region specific selections as varieties from different centers in India, still, varieties suited to coastal eco-system are yet to be identified. Hence, an experiment was laid out to study the performance of 21 genotypes of Polianthes tuberosa L. collected from varied geographical locations. The trial was conducted in the floriculture unit of the Department of Horticulture, Faculty of Agriculture, Annamalai University under randomized block design replicated thrice to assess the genetic variability for eleven economic characters. The results showed that the genotype PT-15 recorded relatively superior mean performance with respect to all characters. High PCV and GCV were observed for number of leaves per plant, plant height and rachis length. Low variability in terms of PCV and GCV was observed for length of the flower and time taken for flowering. High PCV and GCV values of more than 60 per cent was observed for bulb volume followed by yield of flowers per plant, rachis length and duration of flowering. The genotypes viz., PT-15 (Kuzhumani, Thiruchirappalli District), PT-3 (Ravanthavadi, Dharmapuri District) and PT-10(Perumalpatti, Dindugul District) were identified as superior genotypes which are suitable for the coastal region based on per se values and can be utilized for future breeding programmes.